1996
DOI: 10.3758/bf03201102
|View full text |Cite
|
Sign up to set email alerts
|

Topographically distinct cortical activation in episodic long-term memory: The retrieval of spatial versus verbal information

Abstract: Two experiments are reported to study slow potentials in the EEG during reactivation of spatial and verbal information. Subjects had to learn associations between drawings and one, two, or three mediators (locations in Experiment 1, nouns in Experiment 2). During recall, subjects had to decide whether or not two drawings were linked to each other by a common mediator. EEG was recorded during learning and recall. Both experiments were completely equivalent. Irrespective of the quality of the mediators, response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…(2) Are these neural correlates of orientation, should they exist, distinct from the neural correlates of effort? As noted by Rugg and Wilding (2000), however, evidence addressing these questions is sparse because almost all potentially relevant studies have confounded either orientation and effort or pre-and postretrieval processing (by failing to separate neural activity elicited by cues eliciting successful vs. unsuccessful retrieval; e.g., Heil, Rösler, & Hennighausen, 1996). Findings from two ERP studies in which these confounds were avoided suggest that different retrieval orientations are neurally dissociable (Johnson, Kounios, & Nolde, 1997;Wilding, 1999; see also Ranganath & Paller, 1999), but the findings do not speak to the question of whether the effects of orientation vary according to effort.…”
mentioning
confidence: 99%
“…(2) Are these neural correlates of orientation, should they exist, distinct from the neural correlates of effort? As noted by Rugg and Wilding (2000), however, evidence addressing these questions is sparse because almost all potentially relevant studies have confounded either orientation and effort or pre-and postretrieval processing (by failing to separate neural activity elicited by cues eliciting successful vs. unsuccessful retrieval; e.g., Heil, Rösler, & Hennighausen, 1996). Findings from two ERP studies in which these confounds were avoided suggest that different retrieval orientations are neurally dissociable (Johnson, Kounios, & Nolde, 1997;Wilding, 1999; see also Ranganath & Paller, 1999), but the findings do not speak to the question of whether the effects of orientation vary according to effort.…”
mentioning
confidence: 99%
“…The nature of the late effect-Fan 2 pairs producing more negative voltages than Fan 1 pairs over the frontal scalp-is similar in some respects to the negative slow potential observed by Heil et al (1996). Nyhus and Curran (2009) also reported an effect of fan on ERPs over the frontal scalp.…”
Section: Associative Fan Effects and Retrievalmentioning
confidence: 54%
“…Nyhus and Curran (2009) also reported an effect of fan on ERPs over the frontal scalp. Our effect was right-lateralized, whereas Nyhus andCurran (2009) andHeil et al (1996) found that the effect of fan was maximal over the left hemisphere. Our experiment differs from Heil et al (1996) in two important ways.…”
Section: Associative Fan Effects and Retrievalmentioning
confidence: 54%
See 1 more Smart Citation
“…This material specificity in the EEG has already been shown for retrieving faces and spatial positions of the same type as used here (Khader, Heil, & Rösler, 2005; see also Mecklinger, 1998). Therefore, slow waves can be utilized to measure the retrieval of material-specific representations from LTM (see also, e.g., Heil, Rösler, & Hennighausen, 1996). The combination of the direct measure of neural activation via EEG with the precise localization provided by fMRI allows to "cross-validate" the found effects with different methods and to derive a coherent picture of the neural processes underlying interference during LTM retrieval.…”
Section: Methodsmentioning
confidence: 99%